Desafios e conquistas de um aluno que procura a escola aos 55 anos - Assis, Léa Nunes de (2014)
The objective of this search was to comprise how the insertion process occurred, the learning and the feelings experienced by a 55 years old student who has looked for a school for the first time in his life (The Education for Young People and Adults course). For that sought out to understand this student s history of life, as well as the beginning of his way in the school. The Henry Wallon s psychogenetic was the theoretical background used. The results lead us to an affective mediation. In this case it happened by the approach of the teacher and the Literature resources, introducing with great pleasure the student into school, making himself to appropriate the lecture, the written and in consequence boost his self-esteem